2022
DOI: 10.2147/cmar.s348102
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Lymph Node Metastases from Central Nervous System Tumors: A Systematic Review

Abstract: Introduction Lymph node metastasis (LNM) from primary tumors of the central nervous system (CNS) is an infrequent condition, and classically it was thought that CNS tumors could not spread via the lymphatic route. Recent discoveries about this route of dissemination make its knowledge necessary for surgeons and pathologists to avoid delays in diagnosis and unnecessary treatments. The aim of this paper is to review the literature and to discuss the relevant pathogenetic mechanism and the cytologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 127 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Based on all the publications mentioned earlier, the predominant sites of systemic metastases were bone and bone marrow. However, metastases to soft tissues, lymph nodes, or lungs are much rarer [10] (Table 1). Given the presumed absence of lymphatic vessels within the central nervous system, the mechanism by which central nervous system tumors spread to lymph nodes remains incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Based on all the publications mentioned earlier, the predominant sites of systemic metastases were bone and bone marrow. However, metastases to soft tissues, lymph nodes, or lungs are much rarer [10] (Table 1). Given the presumed absence of lymphatic vessels within the central nervous system, the mechanism by which central nervous system tumors spread to lymph nodes remains incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…One of the largest studies carried out by Coca‐Pelaz et al on cervical lymph node metastasis of CNS tumors consisted of 172 cases out of which 12 cases were of oligodendroglioma (including anaplastic oligodendroglioma) and all the cases had a previous history of CNS tumor 12 …”
Section: Discussionmentioning
confidence: 99%
“…One of the largest studies carried out by Coca-Pelaz et al on cervical lymph node metastasis of CNS tumors consisted of 172 cases out of which 12 cases were of oligodendroglioma (including anaplastic oligodendroglioma) and all the cases had a previous history of CNS tumor. 12 To date, the cytological features of oligodendroglioma or anaplastic oligodendroglioma have been described based on touch or squash smears of primary brain tumors. Watson and Hajdu first defined cytomorphologic findings of primary OG as uniform cells with round nuclei and prominent nucleoli on touch smears.…”
Section: Discussionmentioning
confidence: 99%
“…Extra-CNS metastases from GB more commonly occur in lymph nodes (LN), lungs, pleura, soft tissues, glands, liver, and bone (10). Coca-Pelaz et al (11), recently conducted a systematic review of the literature published in the period 1944-2021, finding 174 cases of LN metastases from primary CNS tumors, with 52.8% being of glial origin. In this series other sites of distant metastases were bones (23%), lungs (11.5%) and non-cervical LN (11%).…”
mentioning
confidence: 99%
“…As this case and prior reports demonstrate, recurrent GB with extra-CNS metastases has very few treatment options. Exceptions to this rule are regional relapses such as those occurring in the dura and head and neck LN, or in oligometastatic bone metastases, which various reports have shown that may be subjected to local treatments achieving longer local and systemic controls (10,11,15,26). Considering that systemic therapy has not demonstrated to prolong OS in patients with recurrent GB, its management is even more complex in patients with extra-CNS metastases.…”
mentioning
confidence: 99%